Functional outcome after pouch-anal reconstruction with primary and secondary mucosectomy for patients with familial adenomatous polyposis (FAP) - Ganschow, Petra; Treiber, Irmgard; Hinz, Ulf (Langenbeck's archives of surgery, 2019)
Introduction: Restorative proctocolectomy and ileal pouch-anal reconstruction is the surgical standard for the majority of patients with familial adenomatous polyposis (FAP). The pouch-anal anastomosis may be performed handsewn after primary mucosectomy or by double stapling. Better functional results favour the latter; however, higher rates of remaining rectal mucosa with adenomas often necessitate secondary mucosectomy. Data on functional outcome after secondary mucosectomy is scarce. The aim of the study was to analyse whether patients who undergo secondary mucosectomy maintain their functional benefits compared to patients with primary mucosectomy. Patients and methods: Twenty patients after secondary mucosectomy and 31 patients after primary mucosectomy were compared with respect to their functional outcome, using the MSKCC score, the Wexner score and ano-rectal physiology testing. Results: The MSKCC global score and the Wexner score showed a non-significant trend towards slightly better results after secondary mucosectomy (63.1 vs. 56.6, p = 0.0188 and 9.5 vs. 11, p = 0.3780). Patients after secondary mucosectomy also showed a tendency towards less bowel movements per 24 h (7 (range 4-11) vs. 8.5 (range 3-20), p = 0.1518). Resting pressures were slightly higher after secondary (44 vs. 39.6 mmHg, p = 0.4545) and squeeze pressures slightly higher after primary mucosectomy (87.6 vs. 81.2 mmHg, p = 0.6126). However, the results did not reach statistical significance. Conclusion: The results of this study cannot ultimately resolve the controversy concerning handsewn versus stapled ileal pouch-anal anastomosis. Our results suggest a trend towards better functional results after stapled anastomosis with secondary mucosectomy.